Body RemiXer: Extending Bodies to Stimulate Social Connection in an Immersive Installation - Desnoyers-Stewart, John; Stepanova, Ekaterina R.; Riecke, Bernhard E.; Pennefather, Patrick (Leonardo, 2020)
Body RemiXer is a mixed reality installation that connects immersants across the virtual/actual divide through emergent tactility and abstract embodiment. Using a virtual reality headset, Kinect and projections, the installation explores the potential of immersive technology to create copresent experiences that foster intercorporeal relationships between immersants wearing a headset and those using the projections. Immersants’ bodies are at the center of the installation, activated as a site for social exchange. Body RemiXer has been exhibited at an art festival and at several smaller events. The authors’ observations during these exhibits reveal Body RemiXer's capacity to disrupt social norms and stimulate new connections.
Keywords: Riecke; Riecke_2020; bernhard-riecke; body-remixer; john-desnoyers-stewart; journalPaper; katerina-stepanova; patrick-pennefather; thesis-related